Stress-based topology optimization of continuum structures under harmonic force excitation. (November 2022) - Han, Yongsheng
Highlights: Structural multidisciplinary design and optimization are achieved. Stress optimization model of structure under harmonic load is proposed. Sensitivity of stress optimization under harmonic excitation are derived. Stress concentration effects are effectively solved. Strength of engineering structure under harmonic load is improved. Abstract: In this paper, a new optimization method for the maximum von Mises stress minimization design of continuum structures subjected to harmonic force excitation is proposed. By using an extended Bi-directional Evolutionary Structural Optimization (BESO) method, the intermediate density elements with high stress state are avoided. To reduce the computational cost, the global von Mises stress is approximately measured by using a global stress measure based on the p -norm. Both sensitivities and topological variables are filtered to overcome the highly nonlinear stress behavior and stabilize the optimization procedure. A series of comparisons have been conducted to validate the effectiveness and practicability of the method on two-dimensional and three-dimensional benchmark design problems. The influence of varying excitation frequencies, damping and boundary conditions on the optimized results and the mode shapes are considered. The optimized results indicate that the proposed approach has good convergence and can achieve a reasonable design that effectively reduces the stress concentration effect at the critical stress areas. Strength of engineering structure under harmonic load is improved.